2021
DOI: 10.1021/acs.jpcc.0c08720
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phase Separation on Rayleigh-Plateau Type Instabilities in Alloys

Abstract: Classical molecular dynamics (MD) simulations are used to investigate the role of phase separation (PS) on the Rayleigh-Plateau (RP) instability. Ni−Ag bulk structures are created at temperatures (2000 K and 1400 K) that generate different PS length scales, λ PS , relative to the RP instability length scale, λ RP . Rectanguloids are then cut from the bulk structures and patterned with a perturbation of certain amplitude and wavelength, λ RP . It is found that when λ PS ≪ λ RP (2000 K), the patterned rectangulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Figures 2(a) and (b) show phase plane plots of T peak and LL, respectively, for various values of substrate thickness H s and Biot numbers, Bi; see Eq. (9). A zero Biot number corresponds to a perfectly insulated substrate that loses no heat to the underlying Si slab, while Bi → ∞ corresponds to a poorly insulated substrate in contact with a Si slab at ambient temperature, T a (in Eq.…”
Section: B Flat Film Results -Influence Of Substrate Thickness Biot N...mentioning
confidence: 99%
See 2 more Smart Citations
“…Figures 2(a) and (b) show phase plane plots of T peak and LL, respectively, for various values of substrate thickness H s and Biot numbers, Bi; see Eq. (9). A zero Biot number corresponds to a perfectly insulated substrate that loses no heat to the underlying Si slab, while Bi → ∞ corresponds to a poorly insulated substrate in contact with a Si slab at ambient temperature, T a (in Eq.…”
Section: B Flat Film Results -Influence Of Substrate Thickness Biot N...mentioning
confidence: 99%
“…A particular challenge involves modeling external effects that couple to the fluid dynamics of the film. Some examples include the influence of an electric field on film dynamics [3][4][5], the competition between chemical instabilities in multi-mixture liquids and their dewetting [6][7][8][9][10], or the effect of permeable underlying substrates [11,12]. Thermal effects have received significant attention as well, in particular regarding the temperature dependence of material properties, as discussed further below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, linear stability analysis predicts a preferred wavelength that will drive a liquid wire to breakup. Much work has been done in regards to nanocluster stability during solid-liquid coexistence 13 , and the stability of liquid nanojets 14,15 , nanocylinders 16 , and even in cylindrical metal alloys 17 , relatively few studies address the stability of the solid core of nanowires close to their melting point. It was found that for finite-sized cylinders during phase coexistence, differences in curvature and fluctuations would lead to the formation of random breaches at the material interface, causing the growth of instabilities which lead to the melting of the solid 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the creation of crystalline phases driven by PR mechanism has been demonstrated, so far there are many open questions. Just few examples include the role of impurities on coupling formation and local atomic site configuration, 14 how these necklace structures are joined to form decorated architectures, [15][16][17] whether there is a full control over composition, diffusion paths, and/or structural modifications, [18][19][20] coexisting structural polytypes, 21,22 diffusion-driven effects, 23 phase separation problems, 24 radial or axial chemical modulations, 22 as well as atomic scale variability due to fluctuations in the growth rate. 4 Consequently, apart from a few cases in which single crystal X-ray diffraction measurements of nanowires could be recorded, [25][26][27] almost no information about the crystal symmetry of individual nanostructures and their integration into single architectures is available.…”
mentioning
confidence: 99%